The adventures of Batman [videorecording (Blu-Ray)] (Warner Bros. Entertainment Inc., 2022)
Get ready to swing into action with this collection of classic crime-fighting fun! Revered by cartoon fans and originally produced by Filmation Studios, these 34 exciting adventures. Join the dynamic duo as they take the fight to criminals all across Gotham City. And what a cast of criminals it is. From foiling Joker's many twisted plans to keeping Catwoman, The Riddler, and The Penguin behind bars.